Nitrogen-coordinated single Fe sites for efficient electrocatalytic N2 fixation in neutral media. (July 2019) - Lü, Fang; Zhao, Shunzheng; Guo, Ruijie; He, Jia; Peng, Xianyun; Bao, Haihong; Fu, Jiantao; Han, Lili; Qi, Gaocan; Luo, Jun; Tang, Xiaolong; Liu, Xijun
Abstract: Electrocatalytic nitrogen reduction reaction (NRR) for NH3 generation under ambient conditions presents a promising alternative to the conventional Haber–Bosch process. Here, we report a Fe single-atom catalyst for ambient electrochemical NH3 synthesis. This catalyst achieves high Faradaic efficiency (18.6 ± 0.8%) and NH3 yield rate (62.9 ± 2.7 μg h −1 mgcat. −1 ) in neutral aqueous electrolyte at room temperature and −0.4 V versus reversible hydrogen electrode. Furthermore, this catalyst exhibits a negligible activity decay during electrolysis for 24 h. X-ray absorption fine structure analyses and theoretical calculations reveal that atomically dispersed single Fe species are stabilized by N in Fe–N4 configuration, which is favorable for N2 activation. This work opens new opportunities for developing advanced single atomic site catalysts for NH3 synthesis via NRR. Graphical abstract: Single Fe active sites supported on N-doped carbon frameworks are reported as a robust electrocatalyst for N2 -to-NH3 conversion with a faradaic efficiency of 18.6 ± 0.8% and a stable activity of more than 24 h. Experiments combined with theoretical calculations reveal that atomically dispersed Fe–N4 sites can activate N2 molecules. Image 1 Highlights: Single Fe atoms showed superior electrocatalytic activity toward N2 reduction in neutral media. The as-prepared catalyst also demonstrated an excellent stability during the electrolysis. Theoretical studies confirmed that atomically dispersed Fe–N4 sites can activate the N2 molecules.